Static behavior of plain journal bearings with textured journal - Experimental analysis. (July 2021) - Filgueira Filho, I.C.M.; Bottene, A.C.; Silva, E.J.; Nicoletti, R.
Abstract: The search for more efficient machines leads to the reduction of friction in the lubricated contacts. One of the ways of achieving this goal is by texturing the surface of the contact. Much has been learned from textures imposed to the bearing casing or pads (static part of the lubricated contact), but there is still a gap in the knowledge of textured journals (moving part of the contact) and their resultant effects on the performance of the bearing. In this work, we present the experimental analysis of a journal bearing whose journal is textured with four different patterns: chevron, saw tooth, oblong dimple, and aligned dimple. Such patterns were imposed to the surface of the journal by the pattern grinding technology. We analyze the resultant eccentricity, attitude angle, and the driving torque of the journal for different operating conditions of the bearing (different Sommerfeld numbers). The obtained results show that the chevron pattern and the oblong dimple pattern present the biggest effects on the studied parameters. Such effect can be either positive or negative depending on the direction of motion of the pattern in the bearing (for unsymmetrical patterns). The aligned dimple texture did not present any significant effect on the bearing performance in comparison to the untextured case. Graphical abstract: Image 1 Highlights: Textures on the journal can result in higher bearing load carrying capacity. Effects depend on the direction of motion of the unsymmetrical patterns. Chevron texture has significant effects due to fluid pumping caused by its geometry. Dimples increase load capacity without affecting attitude angle and driving torque. The saw tooth texture presents smaller effects on the parameters.